Naked villainy: Encounters with an archetype of disfigurement. Issue 1 (1st June 2021) - LaMontagne-Schenck, Ben
This research report is focused on an emergent methodology developed to support a transformational actor‐researcher engaged in heuristic inquiry. Rooted in Stanislavskian practices, transformational acting outlines a character building technique that is, at its core, a physical process. By including costume as an integral component of this physical character-building process, the actor is equipped with a material tool with which they may alter their means of perception. A combined reading of modern cognitive theory and feminist theory asserts that such perceptual alterations as costume affords may then result in a fundamental shift in the performer's identity, facilitating a lived experience of the character's identity. Considering costume within a Stanislavskian context introduces a material set of given circumstances; an embodied experience of another's possibilities or impossibilities of movement. While these perceptual changes stimulate transformation, an actor‐researcher may also find themselves in active collaboration with a 'character' outside of themselves, potentially lending new-found insight within a research setting. Starting from a materialist approach to character, I chose to use Shakespeare's character Richard III as a case study to test my hypothesis. What I soon began to realize was that this unidentified 'materiality' that I had been drawn to could not be distinguished from Richard's 'disability'. I began to ask, what are the ethical implications of an actor donning various external costume-based tools in embodying a disabled character? How does such an approach help us move away from the medical model of disability to the social, and perhaps even towards the affirmative and to resituate disability as a lived experience rather than metaphor? This research report details an emergent methodology confronted with the ethical implications of costume's impact on the portrayal and understanding of disability in theatre today.